2017
DOI: 10.1016/j.hrthm.2017.06.038
|View full text |Cite
|
Sign up to set email alerts
|

Electrotaxis of cardiac progenitor cells, cardiac fibroblasts, and induced pluripotent stem cell-derived cardiac progenitor cells requires serum and is directed via PI3′K pathways

Abstract: Background The limited regenerative capacity of cardiac tissue has long been an obstacle to treating damaged myocardium. Cell-based therapy offers an enormous potential to the current treatment paradigms. However, the efficacy of regenerative therapies remains limited by inefficient delivery and engraftment. Electrotaxis, electrically guided cell movement, has been clinically utilized to improve recovery in a number of tissues, but has not been investigated for treating myocardial damage. Objectives The goal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(26 citation statements)
references
References 29 publications
9
17
0
Order By: Relevance
“…The minimum intensity of the electric field ( ) is obtained for the PZE fiber with the minimum thickness ( ), and the maximum electric field ( ) is obtained for the PZE fiber with the highest thickness ( ). This range of electric fields is within the range of those that can be found in the bibliography [ 17 , 54 , 87 , 88 , 89 ]. In this way, it is possible to combine the mechanical and electrical stimulation of the cells, by tuning the imposed deformation on the PZE fiber with its thickness.…”
Section: Materials and Methodssupporting
confidence: 65%
See 3 more Smart Citations
“…The minimum intensity of the electric field ( ) is obtained for the PZE fiber with the minimum thickness ( ), and the maximum electric field ( ) is obtained for the PZE fiber with the highest thickness ( ). This range of electric fields is within the range of those that can be found in the bibliography [ 17 , 54 , 87 , 88 , 89 ]. In this way, it is possible to combine the mechanical and electrical stimulation of the cells, by tuning the imposed deformation on the PZE fiber with its thickness.…”
Section: Materials and Methodssupporting
confidence: 65%
“…Furthermore, the migration velocity seems to be proportional to the intensity of the ES until a saturation point is reached, for which the velocity is maintained even with the increase in the ES [ 53 ]. B. Frederich et al observed that different cardiac cells show a proportional response to the electric field intensity [ 54 ]. Thus, we consider the electric forces, , due to the ES, proportional to the electric field, E , as [ 50 , 51 ] where E is the magnitude of the electric field.…”
Section: Materials and Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…EFs could redistribute integrin a5b1 toward the trailing edge in cathodal-migrating fibroblasts (63). It is also reported that integrin a4b1 is required for anodal electrotaxis and localizes to the front edge of cardiac progenitor cells (64). Integrin b1, one of the key subunits of integrin receptors, has been found to be involved in the electrotaxis by polarization and activation of several kinds of cells, including fibroblasts (65), epithelial cells (66), keratinocytes (67), and fish keratocytes (68).…”
Section: Discussionmentioning
confidence: 98%